Reforming Police Oversight after Kanjuruhan Tragedy: A Comparative Study of Indonesia and the United Kingdom - Shibghatullah , Muhammad Agil; Sholahuddin Al Fatih; Wibisono, Rizky Bangun (Hang Tuah Law Journal, 2026)
This study examines police accountability and institutional oversight within the Indonesian National Police (Polri) following the Kanjuruhan Tragedy, focusing on the relationship between police authority, human rights protection, and democratic governance. Employing a normative juridical method with statutory, conceptual, and comparative approaches, the study analyzes Indonesia’s legal framework and compares it with oversight mechanisms in the United Kingdom. The analysis is grounded in the principles of the rule of law, checks and balances, proportionality in the use of force, and the International Covenant on Civil and Political Rights (ICCPR). The findings reveal that Polri’s institutional design as an autonomous state institution directly accountable to the President provides considerable operational independence in maintaining public order and security. However, this institutional autonomy is not matched by sufficiently independent and effective external oversight, resulting in an accountability gap over the exercise of coercive police powers. The Kanjuruhan Tragedy demonstrates how deficiencies in command responsibility, supervision, and compliance with human rights-based use-of-force standards may lead to serious violations of the right to life and personal security. From an ICCPR perspective, these shortcomings reflect the State’s failure to fulfill its positive obligation to prevent arbitrary deprivation of life during public assemblies. Comparative analysis with the United Kingdom indicates that democratic policing requires a balance between operational independence and robust accountability through independent civilian oversight, transparent investigations, parliamentary scrutiny, judicial review, and accessible complaint mechanisms. Accordingly, this study proposes an integrated accountability reform by strengthening Kompolnas, enhancing parliamentary and judicial oversight, improving disciplinary transparency, expanding civilian participation, and utilizing technology-based monitoring. These reforms are essential to align police authority with constitutional principles, the rule of law, and international human rights standards while restoring public trust in Polri.